Analisis Perbedaan Kandungan Pigmen Klorofil pada Beberapa Varietas Sayuran (Lactuca sativa dan Amaranthus sp.) - Aura Alfisyahrin; Diyah Anjani; Diah Khairani; Jeli Parsela; Tri Mustika Sarjani (Symbiotic: Journal of Biological Education and Science, 2025)
Chlorophyll is the primary pigment in plants. Most chlorophyll is found in leaves, and its content varies among different leaves. Chlorophyll functions as an antioxidant for the body. Plants rich in chlorophyll include spinach and lettuce. Spinach and lettuce are popular vegetables among the public due to their high nutritional value. This study aims to determine the differences in chlorophyll content between these two types of vegetables. The research was conducted in the Basic Laboratory of Universitas Samudra using a spectrophotometer to identify the chlorophyll content in lettuce and spinach, determined through calculation methods. The results showed a significant difference in chlorophyll content between spinach and lettuce, particularly between green and red varieties. Green spinach had the highest chlorophyll content, whereas red lettuce had the lowest. This difference is due to pigment variations, where chlorophyll is more dominant in green varieties, while anthocyanin is more dominant in red varieties. Chlorophyll extracts from these vegetables have great potential as a natural antioxidant source that supports overall health, making them an important part of a daily diet.